2021
DOI: 10.1177/03331024211056580
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of idiopathic intracranial hypertension - the importance of excluding secondary causes: A systematic review

Abstract: Background Idiopathic intracranial hypertension is characterized by increased intracranial pressure without any pathological findings on neuroimaging, except for signs of high intracranial pressure. Before diagnosing idiopathic intracranial hypertension secondary causes of increased intracranial pressure should be excluded. Objective to characterize the phenotype of patients with secondary intracranial hypertension and to identify possible risk factors for secondary intracranial hypertension. Methods We have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 117 publications
(214 reference statements)
0
7
0
Order By: Relevance
“…In a systematic review tetracycline class antibiotics and retinoids had the highest number of reported cases of medication induced sPTCS with !20 cases (12). Prednisolone has mostly been associated with sPTCS in children in previous studies (12,18). For two patients categorized as 'several competing causes known to cause sPTCS' debut of sPTCS was associated with both prednisolone treatment and renal failure.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a systematic review tetracycline class antibiotics and retinoids had the highest number of reported cases of medication induced sPTCS with !20 cases (12). Prednisolone has mostly been associated with sPTCS in children in previous studies (12,18). For two patients categorized as 'several competing causes known to cause sPTCS' debut of sPTCS was associated with both prednisolone treatment and renal failure.…”
Section: Discussionmentioning
confidence: 94%
“…males, post-menopausal females or BMI <30. Previous studies investigating sPTCS have primarily been case studies or retrospective studies and only one recent literature review has reviewed various causes of sPTCS (18). Interestingly this study found that among sPTCS cases, 70.9% were female and 40.4% had a BMI >25 (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Many risk factors for IIH have been established, including medication use (tetracycline antibiotics, retinoids) and medical disease (endocrinopathies, leukemia, iron deficiency anemia), but the link between SCD or hydroxyurea use and IIH remains unclear. 9 Among all previously published cases of IIH in patients with SCD, the patients have been either prepubertal or obese. 5 - 8 …”
Section: Discussionmentioning
confidence: 99%
“…Given that IIH is rarer in prepubertal children, and potentially has a different underlying pathogenesis (32), the present guidelines will primarily focus on those postpuberty and adults. The present guidelines will only address IIH and not secondary pseudotumor cerebri syndrome nor Idiopathic Intracranial Hypertension without Papilledema (IIHWOP) as these are rare conditions with likely alternative underlying pathophysiology (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%